Hedging no modelo com processo de Poisson composto - Sung, Victor Sae Hon (Universidade Federal de São Carlos, 2015)
The investor, that negotiate assets, is subject to economic risks of any negotiation because there is no certainty regarding the appreciation or depreciation of an asset. Here comes the futures market, where contracts can be negotiated in order to protect (hedge) the risk of excessive losses or gains, making the purchase or sale assets, fair for both sides. The goal of this work consist in study Lévy pure-jump process with finite activity, also known as compound Poisson process, and its applications. Discovered by the French mathematician Paul Pierre Lévy, the Lévy processes admits jumps in paths, which is often observed in financial markets. We will define a hedging strategy for a market model with compound Poisson process using mean-variance hedging and dynamic programming.
Hedging in compound Poisson process model
Keywords: Mercado futuro; Princípio da programação dinâmica; Modelo com processo de Poisson composto; Mean-variance hedging; Hedging; Processo de Poisson composto; Futures; Compound Poisson process; Dynamic programming; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA